2015
DOI: 10.1016/j.jinorgbio.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and induction of apoptosis in pancreatic cancer cells by a new dinuclear bis(triazacyclonane) copper complex

Abstract: The dinuclear copper(II) complex [Cu 2 {bcmp(-H)}(μ-OH)](NO 3 ) 2 ·H 2 O (1, bcmp = 2,6-bis(1,4,7-triazacyclonon-1-ylmethyl)-4-methylphenol) has been synthesized and characterized by electrospray ionization mass spectrometry, potentiometric titration and cyclovoltammetry. The X-ray structure of the analogous perchlorate salt [Cu 2 {bcmp(-H)}(μ-OH)](ClO 4 ) 2 ·2.5H 2 O (2) was determined. Cytotoxicity studies showed very promising activity of 1 against various pancreatic tumor cell lines with IC 50 values compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
0
33
1
3
Order By: Relevance
“…Several studies demonstrated that cisplatin-induced cytotoxicity culminates in the activation of apoptosis in cancer cells [34][35][36] . The activation of apoptosis occurs through a mitochondrial membrane potential change and caspase-3 activation 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that cisplatin-induced cytotoxicity culminates in the activation of apoptosis in cancer cells [34][35][36] . The activation of apoptosis occurs through a mitochondrial membrane potential change and caspase-3 activation 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Their complex interacts with DNA and activates the p53-dependent pathway of apoptosis. 17 Zhu and co-workers reported potent antitumoral activity against human cell lines (A549, Eca109 and SGC7901) for three mononuclear complexes containing the ligand H 2 TBHP (2-(3,5-di-tert-butyl-2-hydroxybenzylamino)-2-benzyl-acetic acid). The associated apoptosis is related to the effect of these copper(II) complexes on the expression of p53, Bax and Bcl-2.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Under these conditions, the fluorescence intensity of the respective complexes, extracted HC‐DNA and ethidium bromide (EtBr) was very small and could be ignored. The interaction of the respective complexes with DNA in vitro was studied as described in the literature …”
Section: Methodsmentioning
confidence: 99%